Island of fire - McMann, Lisa (McMann, Lisa. Unwanteds, 2013)
The magical world of Artime is gone and the Unwanteds are looking to Alex Stowe for answers, but while his twin brother Aaron continues to build his army in Quill, a very dangerous common enemy is revealed.